2014
DOI: 10.1080/17429145.2014.918663
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and associations of dominant woody species in desert–oasis ecotone of South Junggar Basin, NW China

Abstract: Spatial patterns and associations of plant species are important for revealing how species interact with each other and with the environment, and hence have important implications for the understanding of species interaction and underlying ecological processes with apparent patterns in temperate desert vegetation. In this paper, the function g (r) was used to characterize the spatial patterns and associations of four dominant woody species in three 1-ha desert plant plots in the desert-oasis ecotone of South J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…However, some disturbances (e.g. fires, anthropogenic activities, introduction of invasive species, megaherbivores' damages) may occur and alter the original SP and thus the underlying processes (Chu, Wang & Zhang, ; Riginos et al ., ). From a demography perspective, these disturbances may induce growth, stability or decline of the populations (Schmidt et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some disturbances (e.g. fires, anthropogenic activities, introduction of invasive species, megaherbivores' damages) may occur and alter the original SP and thus the underlying processes (Chu, Wang & Zhang, ; Riginos et al ., ). From a demography perspective, these disturbances may induce growth, stability or decline of the populations (Schmidt et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable forest management in arid and semi-arid areas has long been interested in managing interspecific relations dominated by desert woody species, but intraspecific competition also is a very important question [34]. In this paper, we showed that intraspecific competition was an important process in four different life stages (seedlings, juveniles, mature, overmature) in a H. ammodendron population in the Ecotone desert-oasis of South Junggar Basin.…”
Section: Implications For Population Managementmentioning
confidence: 84%
“…Micro-topography creates biotic heterogeneities (e.g., seed tree abundance, intraspecific competition) and abiotic heterogeneities (e.g., soil organic, salt, water), which act as a filter for seed availability, seedling germination, and establishment in arid and semi-arid environments [27,34]. Thus, for H. ammodendron with limited seed dispersal distance, seed availability may be the main limiting factor for recruitment in severely heterogeneities topography areas and result in competitive relation and aggregated patterns in desert areas [11].…”
Section: Implications For Population Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the spatial differentiation characteristics of grassland patches is the most direct and practical method for assessing ecosystem status (Kefi, Alados, 2010). It is closely related to ecosystem function and promotes the understanding of ecological phenomena covered by spatial pattern representation (Meloni, Granzotti, 2017), so as to better understand the succession characteristics of patches in alpine grassland degradation process (Chu, Wang, 2014). In the region where this study is located, the ecological pressure resistance is poor and the aggregation scale gradually decreases, thus forming a patchy spatial pattern.…”
Section: Discussionmentioning
confidence: 99%